Suriname : Staff Report for the 2014 Article IV Consultatio. (IMF Staff Country Reports; Country Report, 2014)
This 2014 Article IV Consultation highlights that Suriname's macroeconomic conditions weakened in 2013 as gold and oil prices declined. With those prices falling below recent peaks, the large fiscal and external sector exposures to the mineral sector continued their deterioration in 2013, along with a significant decline in international reserves. Growth is estimated at a robust 4 percent in 2013, supported by fiscal relaxation and strong credit growth. Strong fiscal consolidation is being implemented in 2014, and the fiscal deficit is expected to decline to 3.7 percent of GDP this year. Public debt is rising but remains relatively low at about 30 percent of GDP.